Some economically important properties of sunflower cultivars (Helianthus annuus L.) in the field trials performed at Biotechnical faculty - Darja KOCJAN AČKO (Acta Agriculturae Slovenica)
The basic parameter of re-introduction of this crop into the crop rotation in Slovenia is testing and trials of sunflower cultivars (Helianthus annuus L.), that could be suitable for the growing conditions in Slovenia, for the purpose of organic production and for the production of healthy food for consumers. On the experimental field at Biotechnical Faculty, in the period from 2002 to 2006, we were testing certain economically significant properties of five sunflower cultivars: Kernal, Kongo, Delija, Goleador and Iregi szürke csíkos. Seeds were sown by hand to the parcel in the size of 3 m x 11.8 m. Under the growing conditions in central Slovenia the genetic potential of hybrids for the production above 4 t of seed/ha was almost reached and closely approached by the hybrids Kongo and Kernal with average yields 3.5 t/ha and 3.3 t/ha. Yields of Delija and Goleador hybrids were about 1 to 1.2 tons lower, but mutually comparable. The lowest yield (1.6 t/ha) was given by Iregi szurke csikos variety, which is mostly grown by the producers in Slovenia, mainly because it is used and sold as a bird feed. In the year 2003, the fat content in the seed obtained from the hybrids, reached from 38 to 42 %, for Iregi szurke csikos variety it was only 33 %, on the other side - in the year 2005 - the fat content in the seed obtained from the hybrids was higher, that is 39 to 45 %, and for the Iregi szurke csikos variety the average was the same as in the year 2003. The highest fat content in the seed was reached by highly oleic hybrid Goleador, that is 42 % in the year 2003 and 45 % in 2005; for this hybrid, during this two years of the trials the 78- to 79-percent content of oleic acid in the oil was a little lower than its genetic potential, which is above 80 %. Regarding the use of the crop - for the cold pressed oil - the most important cultivars are the highly oleic hybrid Goleador and semi-oleic Delija, and for the bird feed instead of the Iregi szurke csikos variety we could sow Kongo and Kernal hybrids, not only due to their higher yields, but also due to higher fat content. Experts can advise producers how they can increase their production of seeds and oil only on the basis of tested, high quality and accessible sunflower assortment.